A facile molecular aggregation of isoquinoline based g-C3N4 for high photocatalytic performance under visible light illumination. (August 2022) - Pan, Feng; Sohail, Muhammad; Taha, T.A.; Al-Sehemi, Abdullah G.; Ullah, Sami; AlSalem, Huda Salem; Mersal, Gaber AM; Ibrahim, Mohamed M.; Alenad, Asma M.; Al-Hartomy, Omar A.; Amin, Mohammed A.; Ajmal, Zeeshan; et al.
Highlights: A carbon abundant 2‐D structure material 5, 8-dibromoisoquinoline (BQ) has been integrated as an aromatic organic monomer within carbon nitride (CN) via molecular aggregation process. The BQ copolymerized CN with distinguish characteristics leads to a significant increment in the applied application. The copolymerized samples demonstrating narrowed band gap, high surface area, splendid morphology, and wide optical absorbance which enhanced electron transport ability. The spinal material, i.e., 10BQ/CN exhibited a superior H2 evolution of ten‐fold higher activity and also photodegradation of RhB under visible light driven. Abstract: Graphitic carbon nitride, g-C3 N4 (CN) is regarded as an excellent metal-free semiconductor known for its potential solar fuel generation and pollutant degradation. In this study, a carbon richer substance, (5, 8-dibromoisoquinoline (BQ)) was used to feed its catalytic function through conventional copolymerization (molecular doping) process at 550°C under a nitrogen atmosphere. The incorporation of BQ monomer in the triazine oligomers of CN in turn enhanced the specific surface area, thereby, improving the lifespan of photoexcited charge carriers, decreasing the charge recombination rate, energy bandgap, and altering the optoelectronic characteristics of CN. On average, the rate of hydrogen (H2 ) production over-optimized 10BQ/CN was 710.1 µmol/h much superior and 10 times higher than that of pure CN (71.9 µmol/h). Particularly, the kinetics of the photocatalytic degradation of RhB over 10BQ/CN followed pseudo-order kinetics and the rate constant was three times larger than pure CN. Our results illustrate the crucial importance of conjugated monomers in improving photocatalysis process for future energy demand by providing key steps towards sustainable energy production. Graphical Abstract: Image, graphical abstract .